Factors of Psychological Readiness of Student Youth for Tutoring for People with Disabilities - Гуляєва, Олена; Myloslavska, Olena; Sergienko, Iulia (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
In the time of higher education modernization, which is focused on individual trajectories and the formation of personality on the basis of its capabilities and abilities, a new role is acquired by a new type of activity – tutoring. In European leading countries, this type of support for people with disabilities has proven its effectiveness, but in Ukraine it is not widely known. The article presents the results of an empirical study of the psychological readiness in young students to become tuitors for people with disabilities. The sample was consisted of 68 students O.M. Beketov National University of Urban Economy in Kharkiv. The research has shown that tutoring is a new and exciting phenomenon that gives students the opportunity to experience mentoring, including students with disabilities. At the same time, psychological readiness for such activities is at a low level, which is caused by the insufficient level of awareness of functional responsibilities of a tutor, a clear ultimate goal, and so on. There are four factors in the structure of psychological readiness for tutoring students with disabilities: “Prosocial Orientation to Help”, “Academic Orientation”, “Social Intuition” and “Communicative Competence”. Given the psychological characteristics of students with disabilities, their support should be significantly different from the educational support of relatively healthy students. The data obtained can be included in the development of a comprehensive program to study the psychological readiness for tutoring people with disabilities.